(NkRITIKA I PUBLICISTIKA(B; / s (N~ASTX (B7s - (NpU[KIN(B, (NaLEKSANDR sERGEEWI^s ((NmOSKWA(B: s (NnAUKA(B, s, 1964)
(Nw SBORNIK WO[LI STATXI I ZAMETKI(B, (NNABROSKI(B, (NZAPISI(B, (NKONSPEKTY(B, (NPLANY(B, (NZAMETKI NA POLQH I DR(B.s
rus
Keywords: (NpUBLICISTIKAs; (NkRITIKAs -- (NsTATXIs